Recent variations in soil moisture use efficiency (SMUE) and its influence factors in Asian drylands. (1st November 2022) - Hao, Haichao; Li, Zhi; Chen, Yaning; Xu, Jianhua; Li, Saibo; Zhang, Shuhua
Abstract: Soil moisture use efficiency (SMUE) is an important indicator for evaluating the suitability of plant growth. This study synthetically assesses changes in SMUE in different vegetation types, fraction of vegetation cover, and altitude in the Asian drylands from 2001 to 2019. It also illustrates the inherent mechanisms by which soil moisture(SM) and net primary production (NPP), which are both affected by CO2 and relative humidity (f), influence SMUE. The results show an increase in SMUE over the study period, with annual mean values ranging from 0 to 0.59 (g C/mm). Forested areas have the highest SMUE value, while shrub land has the lowest value. These changes in SMUE are dominated by the three vegetation spatial combination patterns of NPP, SM, and the coupling relationship between NPP and SM. Forests and cropland are dominated by NPP, while wetlands, grassland and shrub land are dominated by SM. NPP is mainly affected by CO2 and the greenhouse effect, whereas SM is mainly affected by f . The results obtained from this study provide scientific data to support the ecological security and development of agriculture and animal husbandry in the Asian drylands, which is critical for maintaining regional ecological stability and sustainable economic and social development.